2003
DOI: 10.26719/2003.9.4.796
|View full text |Cite
|
Sign up to set email alerts
|

Adherence of the private sector to national tuberculosis guidelines in the Islamic Republic of Iran, 2001-02

Abstract: We determined the knowledge and practice of private sector physicians in three cites regarding management of pulmonary tuberculosis [TB] and their determinants. A random sample questionnaire survey was conducted of 732 private physicians. Stratified analysis and logistic regression were used to identify the adjusted determinants of the two outcomes. A high proportion of the doctors had correct knowledge about the major diagnostic criteria but there was a low level of knowledge and practice of TB management. Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…A study conducted in Iran found 50% of clinicians have knowledge of and adhere to correct treatment guidelines [ 11 ]. The results of this study indicate a lack of knowledge, which poses a threat to TB control in the country and can be the reason for emerging as well as spreading drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted in Iran found 50% of clinicians have knowledge of and adhere to correct treatment guidelines [ 11 ]. The results of this study indicate a lack of knowledge, which poses a threat to TB control in the country and can be the reason for emerging as well as spreading drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…2 There are concerns that private providers lack the knowledge to implement proper TB case management. [3][4][5][6] A comparison of TB management in the public and private sectors in Australia noted that private-sector patients were more likely to receive less than 4 first-line medications, but treatment outcomes were comparable between sectors. 6 A study in Nigeria to assess the quality of TB diagnosis and treatment showed that in 2008, when private sector involvement in TB control was still in its early stage, private physicians who had reported managing TB clients had poor knowledge and practice of TB management.…”
Section: Introductionmentioning
confidence: 99%